GENDER EQUALITY IN TEACHING MATERIALS OF ARABIC AT ELEMENTARY SCHOOL - Akmaliyah Akmaliyah; Ridho Rosyid Mohammad; Mughni A. Syafiq (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
To inculcate since the early age concept of gender equality within children is essential and needs to intensify. One way to socialize this concept is through education. Arabic language as a subject formally taught among elementary school students, especially in their integrated system schools, can be utilized as a vehicle for this particular agenda.  A research conducted to study materials being taught in those schools in connection with gender equality is required. This paper is designed using analytic descriptive method to help accomplish that purpose.